2020
DOI: 10.29303/jpm.v15i5.1635
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Berbasis Science, Technology, Environment, Society (SETS) Untuk Meningkatkan Literasi Sains Peserta Didik

Abstract: Literasi sains (scientific literacy) merupakan indikator keberhasilan dalam proses pendidikan, dan salah satu unsur pendukungnya adalah proses pembelajaran yang terintegrasi science, environment, technology, dan society (SETS). Penelitian ini bertujuan  mengembangkan bahan ajar terintegrasi SETS untuk meningkatkan  literasi sains peserta didik kelas VIII di MTsN 1 Mataram. Desain penelitian menggunakan Pre-test post-test Control Group Design dengan metode penelitian adalah Research and Development (R&D). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Multidimensional science learning with integrated SETS can help students practice their scientific literacy skills (Zooler, 2013). Scientific literacy was closely related to the science material itself, the application of technology, the influence of the environment, and the surrounding community so that SETS-based teaching materials can improve students' scientific literacy (Hardianti, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidimensional science learning with integrated SETS can help students practice their scientific literacy skills (Zooler, 2013). Scientific literacy was closely related to the science material itself, the application of technology, the influence of the environment, and the surrounding community so that SETS-based teaching materials can improve students' scientific literacy (Hardianti, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The development of SETS teaching materials that contain religious values, namely I-SETS, has been proven to improve students' religious character, discipline, and responsibility after using teaching materials as learning media (Wahyuni, 2017). The latest research from Hardianti (2021), which developed teaching materials based on (SETS) on the motion system of living things, has been proven to improve the scientific literacy of class VIII students at State Islamic Junior High School 1 Mataram. Based on the description of the development of teaching materials, it showed that the development of teaching materials based on SETS has the potential to increase students' activity, character, care for the environment, and even scientific literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to the theory put forward by J. van den Akker, that the teaching teaching materials imply that learning physics must be a strong foundation that can lead students towards scientific progress and achievement of learning outcomes. Another view is explained by (Hardianti et al, 2020) that in the development of a teaching material, three criteria must be met, namely validity, practicality and effectiveness to obtain a product that is completely successful in substance. Other opinions are also expressed by (Nurdyansyah & Mutala'liah, 2018) regarding the development of learning device.…”
Section: B Effectivenessmentioning
confidence: 99%
“…SETS-based modules are one of various modules that can be inserted in scientific literacy (Nisa et al, 2021;Hardianti et al, 2020;Ulfah et al, 2020). the content or content of the module is very influential on how students think.…”
Section: Introductionmentioning
confidence: 99%